Are there gross motor coordination spurts during mid‐childhood? - Santos, Marcos A. M. dos (2021)
Objectives: The aims of this study were (1) to identify the timing of the mid growth spurt (MGS) in stature in children and (2) to identify gross motor coordina tion (GMC) spurts when aligned by the age of attainment of the MGS (aMGS). Methods: Stature, weight, and GMC were measured in 245 Portuguese children followed annually from 6 to 10 years. GMC was assessed and to estimate children's MGS in stature as well as GMC spurts in each of the four tests aligned by aMGS, we used a nonsmoothed polynomial methodology. Results: In boys, the aMGS was attained at 7.8 years, whereas in girls it was 8.0 years. In boys, the peak MGS was 6.2 cm yr−1 and in girls it was 6.4 cm yr−1 . In boys, the peak for walking backwards (WB) occurred 18 months before aMGS (14.9-points yr−1 ), jumping sideways (JS) was 12 months after aMGS (13.5-points yr−1 ), hopping on one leg (HO) was 18 months before aMGS (11.7-points yr−1 ), and shifting platform (SP) was 12 months before aMGS (6.8-points yr−1 ). In girls, WB spurts occurred 12 months after aMGS (13.3-points yr−1 ), JS was 12 months before aMGS (10.5-points yr−1 ), HO was coincident with aMGS (10.4-points yr−1 ), and SP was 18 as well as 12 months before aMGS (7.2-points yr−1 ). No differences were observed in the mean peak spurts between sexes in the GMC tests. Conclusions: Boys and girls reached their MGS in stature at about the same chro nological age. Spurts in GMC did not express themselves in the same biological timing relative to aMGS in stature, and there are sex differences.